Rare occurrence of a lateral cunieform-cuboid coalition - William Hoffman, DPM; Faith Schick, DPM; Homyar Karanjia, DPM; Nicholas Taweel, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases, 2023)
Tarsal coalitions are a group of osseous anomalies where there is a bridge between two or more bones that normally does not exist. This bridge often results in decreased or abnormal motion which can lead to pain and deformity over time. This case report centers on a 41-year-old male with a rare coalition between the lateral cuneiform and cuboid bones of the foot which was identified on magnetic resonance imaging (MRI) after plain radiographs failed to show any abnormalities. This is believed to be only the fifth account of this coalition in the literature and possibly the first account of this coalition in a male patient. Surgical options were offered to the patient, but he was unable to commit to the post operative requirements of surgery. An ultrasound-guided cortisone injection was offered as an alternative treatment option which did provide adequate pain relief. Surgical options will be revisited in the future if symptoms return. The scarcity of this specific coalition and other rarer coalitions makes reporting on them valuable additions to the literature as limited guidance regarding their treatment currently exists.